Acúmulo de matéria seca e de nutrientes em pimentão adubado com doses de nitrogênio e fósforo - Paulino, Renan da Cruz (2016)
Nitrogen (N) is one of the macronutrients more absorbed by sweet pepper, and phosphorus (P), one of the macronutrients that limit crop production. The experimental design was a randomized block design with four replications. These consisted of the implementation of the five nitrogen rates (0, 50, 100, 150 and 200 kg ha-1 N) and phosphorus than five (0, 60, 120, 200 and 300 kg ha-1 P2O5), in a red yellow podzolic in the municipality of Mossoró in the state of Rio Grande do Norte, Brazil. The following characteristics were evaluated: commercial fruit productivity, non-commercial fruit productivity, overall productivity of fruits, number of commercial fruits, number of unmarketable fruits, total number of fruits and average weight of commercial fruits. It defined the critical level of P extracted from the soil by Mehlich-1 extractor, as well as the critical levels of N and P in the diagnostic leaves. For the growth analysis and nutrient absorption four plants were sampled at 14, 28, 42, 56, 70, 84, 98, 112 and 126 days after transplanting (DAT) at doses of 100 kg ha-1 N and 120 kg ha-1 of P2O5. The maximum production of dry plant matter occurred at 126 DAT, with accumulation of 73.5 g plant-1. For this value, the fruits accounted for 57.1% and vegetative shoots with 42.9%. The accumulation of nutrients in the plant in descending order was: K (2.68 g plant-1) > N (1.61 g plant-1) > Ca (0.31 g plant-1) > Mg (0.23 g plant-1) > P (0.20 g plant-1). Regarding nutrient partitioning in the plant, the N and P were found in large quantities in fruits, while K, Ca and Mg in the vegetative shoot. For productivity of 16.3 t ha-1, exports of N, P, K, Ca and Mg were equivalent to 23.07; 3.41; 29.17; 1.33 and 2.08 kg ha-1, respectively. For this soil, the combination of 29.93 kg ha-1 N and 40.22 kg ha-1 P2O5 was promoted the maximum economic efficiency yield of sweet pepper. The critical levels of N in the sheet and P in leaf and soil associated with producing maximum economic efficiency of sweet pepper were, respectively, 34.78 to 38.94 g kg-1; 2.02 to 2.36 g kg-1 and 12.85 to 29.18 mg dm-3